Reflective observation in the supervised English language internship: a look at learning in a public school in Bragança- PA - SILVA, Elizangela Vieira da (2023)
The present article has as purpose reporting the experiences developed in the Internship High School observation of the High School, the English Language Undergraduation Course at the Federal University of Pará. Where we sought to analyze a class the 2nd year high school, from the public school system, in the city of Bragança-Pa, at the Integral High School Prof. Bolívar Bordallo da Silva. It general aimed to reflect on the experience of the observation internship in high school, from the perspective of the students involved; and for specific goals to analyze how students are encouraged to participate in activities in the English discipline and how they can contribute to the promotion of new knowledge from their experiences. The methodological procedures were based on the analysis of the Observation Internship Report, realizing how the student's relationship with the English discipline took place. For observations, we were guided by a questionnaire on Google Forms, with questions related to different aspects that are experienced by students, such as: if they like the English subject, if they think the time of hours/classes, during the week, favor yours learning, etc. The results showed that the students like the subject of English, but that learning is a great challenge, where the little time of weekly classes makes learning difficult. Moreover, students would like to have more diversified activities. This research is extremely important for the academic community, since the results can contribute to the formation of pre- service teachers.